Jawapan

2015-10-04T21:42:17+08:00
2x^2-3x-p=0
x^2-3/2x-p/2=0

H.T.P                                 H.D.P
2a+a=(-3/2)                     2a(a)=(-p/2)   
3a= -3/2                            2(-1/2)(-1/2)=-p/2
a=-1/2                                       1/2=-p/2
                                             p=(-1)
2015-10-04T21:47:30+08:00
2x^2 = 3x +p
2x^2 -3x -p = 0

HTP = a +2a = 3a
HDP = a (2a) = 2a^2

x^2 -(3/2)x -p/2 = 0
x^2 - HTP + HDP = 0

3a = 3/2
a = 3/2 X 1/3
a = 1/2

2a^2 = -p/2
2 (1/2)^2 = -p/2
2 (1/4) = -p/2
1/2 X 2 = -p
-p = 1
p = -1